2020
DOI: 10.1098/rsif.2019.0374
|View full text |Cite
|
Sign up to set email alerts
|

A general model of locomotion of brittle stars with a variable number of arms

Abstract: Typical brittle stars have five radially symmetrical arms that coordinate to move the body in a certain direction. However, some species have a variable number of arms, which is a unique trait since intact animals normally have a fixed number of limbs. How does a single species manage different numbers of appendages for adaptive locomotion? We herein describe locomotion in Ophiactis brachyaspis with four, five, six and seven arms to propose a common rule for the movement of brittle star… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Body plan can have an important effect on behavior. For example, radially symmetrical species move differently than bilaterally symmetrical species (Hollo and Novak, 2012;Wakita et al, 2020). For example, bilateral symmetry typically results in behaviors that occur in an anterior-posterior orientation, including foraging (Jumars et al, 2015;Kane et al, 2017), locomotion (Hollo and Novak, 2012), and mating (Koshio et al, 2007), whereas radial symmetry leads to no such orientation (Wakita et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Body plan can have an important effect on behavior. For example, radially symmetrical species move differently than bilaterally symmetrical species (Hollo and Novak, 2012;Wakita et al, 2020). For example, bilateral symmetry typically results in behaviors that occur in an anterior-posterior orientation, including foraging (Jumars et al, 2015;Kane et al, 2017), locomotion (Hollo and Novak, 2012), and mating (Koshio et al, 2007), whereas radial symmetry leads to no such orientation (Wakita et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…For example, radially symmetrical species move differently than bilaterally symmetrical species (Hollo and Novak, 2012;Wakita et al, 2020). For example, bilateral symmetry typically results in behaviors that occur in an anterior-posterior orientation, including foraging (Jumars et al, 2015;Kane et al, 2017), locomotion (Hollo and Novak, 2012), and mating (Koshio et al, 2007), whereas radial symmetry leads to no such orientation (Wakita et al, 2020). An important property of bilateral symmetry is that it also allows an individual to express handedness, defined here as the propensity to use one side of the body preferentially over the other (Palmer, 2006;Bryden, 2016); we use the term "handed" in its broad sense as defined in previous work (Hata et al, 2011;Buchanan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Although the basic Bayesian framework and its mathematical foundation of measuring the predictability of an arbitrary pair of a statistical model and a prior distribution, has been rigorously established (Watanabe, 2010b;Watanabe, 2010a;Watanabe, 2018), there are few applications of the framework to behavioral data containing repeated measurements (Wakita, Kagaya & Aonuma, 2020). Specifically, the performance of a predictive distribution can be inferred using the Widely-Applicable Information Criterion (WAIC); it is a measure of the generalization error defined as the extent to which a specified predictive distribution is approximated with respect to an unknown true distribution that generates data (Akaike, 1980;Watanabe, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we concluded that the model evaluation using WAIC was more appropriate than using WBIC. Indeed, WAIC is useful for real data even if we are limited to behavioral data (Wakita, Kagaya & Aonuma, 2020;Barrett, McElreath & Perry, 2017).…”
mentioning
confidence: 99%
“…One large ossicle (the vertebra, formed from fused ambulacrals [ 24 ]) forms the centre of each segment. Living ophiuroids generally coordinate periodic musculoskeletally-driven oscillations of their arms to effect rapid locomotion [ 26 28 ]. Related taxa such as sea stars and sea urchins [ 3 , 4 , 14 , 29 ], by contrast, use tube feet as a primary tool for locomotion.…”
Section: Introductionmentioning
confidence: 99%